2012
DOI: 10.1177/070674371205700606
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Frequency of Mental Health Care Provided by General Practitioners: Differences between 2 National Data Sources for the Same Population

Abstract: GPs saw more than twice as many patients for mental health issues according to administrative data, compared with survey data; however, the number of visits per patient was higher in survey data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…That 20% of patients had a documented mental disorder is consistent with other work involving adm inistrative data, which estimated 19% of patients attending GPs in Canada did so for the care of mental health issues (Palin et al, 2012). However, our estimate is considerably lower than that reported in studies which involved standardised screening measures.…”
Section: Holy This Relates To Other Researchsupporting
confidence: 89%
“…That 20% of patients had a documented mental disorder is consistent with other work involving adm inistrative data, which estimated 19% of patients attending GPs in Canada did so for the care of mental health issues (Palin et al, 2012). However, our estimate is considerably lower than that reported in studies which involved standardised screening measures.…”
Section: Holy This Relates To Other Researchsupporting
confidence: 89%
“…Contextualizing prevalence estimates obtained from either survey or administrative databases is an important component of meaningful comparison and synthesis (11). The goal of our prevalence estimation was to compare diagnosed prevalence estimates from both survey and administrative data, which involves estimating the number of people in the population who meet the criteria for a diagnosis of a mood or anxiety disorder (23,25,34,38). There is currently no gold standard measure of diagnosed mood and anxiety disorders in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate population-based prevalence estimates are important as they directly inform health service planning and resource allocation (24). While available evidence from linked survey and administrative databases suggest there is high discordance for mental health service use, there is currently no available estimates of the concordance of diagnosed mental disorders in Canada (25). This comparison has important implications for our understanding of the burden of mental illness in the population.…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian study found that seniors were most likely to go to their general practitioner for psychological issues (Hardy, Kelly & Voaklander, 2001). Palin, Goldner, Koehoom and Hertzmann (2012) argued that general practitioners are "The main, or often the only, source of mental health care for most Canadians, and are typically the gatekeepers to specialty medical care" (p. 367).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…There may be modifications that could be made to the criteria that would increase their sensitivity/specificity. Palin et al (2012) conducted a study comparing mental health codes found in British…”
Section: Tbi In the Elderly 75mentioning
confidence: 99%